Photodynamic therapy of penile cancer - D. M. Yagudaev; G. P. Gens; Z. A. Kadyrov; A. V. Tikhonenko; N. A. Kalyagina (Biomedical Photonics)
In this article we submit the case report of a patient with cT1N0M0 penile cancer diagnosis. The patient underwent two courses of photodynamic therapy (PDT) using Fotoditazin photosensitizer (PS) and ATKUS-2 diode laser. The PS was administered at a dose of 1 mg/kg of body weight 2 hours prior to the PDT session. The irradiation parameters were: 662 nm laser wavelength, 200 mW/cm2 power density and 250 J/cm2 energy density. In the presented clinical observation, we demonstrated that PDT is an effective and safe treatment method in patients with non-invasive penile cancer. The use of photodynamic therapy allowed preserving the physiological urination, sexual function and achieving a good cosmetic effect.